2016
DOI: 10.1177/0022022116655963
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Repressive Suffering Construal as a Function of Collectivism and Social Morality

Abstract: Prior research demonstrated that an experimentally primed collectivist orientation increased repressive suffering construal (RSC): interpretation of suffering as being caused by deviance and having the purpose of maintaining social order. Furthermore, the effect of collectivism on RSC was mediated by social morality: the belief that society dictates morality. The current research provides the first cross-cultural empirical evidence for the links between RSC, collectivism, and social morality. In an investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Furthermore, the overreliance on U.S. samples and political ideologies is now beginning to be complemented by studies examining how moral concerns may be similar or different in different cultural and political contexts (e.g., Nilson, & Strupp-Levitsky, 2016). Recent work has compared the moral foundations endorsed by Chinese versus U.S. samples (Kwan, 2016), has examined this among Muslims in Turkey (Yilmaz, Harma, & Bakçekapili, & Cesur, 2016), and has made other intercultural comparisons (Stankov & Lee, 2016a, 2016b; Sullivan, Stewart, Landau, Liu, Yang, & Diefendorf, 2016). This helps understand that some moral concerns emerge consistently across different cultural contexts, and the macro-level cultural values and corruption indicators that characterize them (Mann, Garcia-Rada, Hornuf, Tafurt, & Ariely, 2016).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Furthermore, the overreliance on U.S. samples and political ideologies is now beginning to be complemented by studies examining how moral concerns may be similar or different in different cultural and political contexts (e.g., Nilson, & Strupp-Levitsky, 2016). Recent work has compared the moral foundations endorsed by Chinese versus U.S. samples (Kwan, 2016), has examined this among Muslims in Turkey (Yilmaz, Harma, & Bakçekapili, & Cesur, 2016), and has made other intercultural comparisons (Stankov & Lee, 2016a, 2016b; Sullivan, Stewart, Landau, Liu, Yang, & Diefendorf, 2016). This helps understand that some moral concerns emerge consistently across different cultural contexts, and the macro-level cultural values and corruption indicators that characterize them (Mann, Garcia-Rada, Hornuf, Tafurt, & Ariely, 2016).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…For the most part, scholars have demonstrated that Westerners tend to sanction criminals to balance the scales of justice (i.e., give criminals their “just desserts”), supported by research on just-world theory (Carlsmith, Darley, & Robinson, 2002; Lerner, 1980). However, research by Sullivan and coauthors (2016) suggests that collectivists may be more likely than individualists to sanction criminals to deter transgressions and preserve social harmony. Our findings suggest that if one’s focus is on maintaining social harmony, then perhaps deterrence is more psychologically important for the role of sanctions.…”
Section: Discussionmentioning
confidence: 99%
“…For collectivists, behaviors that threaten or violate the sanctity of the collective are immoral and deserve punishment (see also Haidt, Koller, & Dias, 1993; Kwan, 2016). In line with this reasoning, recent research demonstrates that Chinese morality is primarily grounded in notions of civility and behaving in a socially appropriate manner (Buchtel et al, 2015) and that Chinese individuals tend to believe that the purpose of punishment is to preserve the greater good of society (Sullivan et al, 2016).…”
Section: Cultural Differences In Determinants Of Responsibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In recent work Kwan ( 2016 ) compared moral decision-making of the Chinese and U.S. culture. Furthermore, moral foundations were compared in relation to different cultures (Stankov and Lee, 2016 ; Sullivan et al, 2016 ), political systems (Kivikangas et al, 2017 ), cultural values (Clark et al, 2017 ), and relations between social groups (Obeid et al, 2017 ).…”
Section: Assumptions and Backgroundmentioning
confidence: 99%